Anterior Hox Genes and the Process of Cephalization - Hombría, James C.-G.; García-Ferrés, Mar; Sánchez-Higueras, Carlos (Frontiers in Cell and Developmental Biology, 2021)
During evolution, bilateral animals have experienced a progressive process of cephalisation with the anterior concentration of nervous tissue, sensory organs and the appearance of dedicated feeding structures surrounding the mouth. Cephalisation has been achieved by the specialisation of the unsegmented anterior end of the body (the acron) and the sequential recruitment to the head of adjacent anterior segments. Here we review the key developmental contribution of Hox1-Hox5 genes to the formation of cephalic structures in vertebrates and arthropods and discuss how this evolved. The appearance of Hox cephalic genes preceded the evolution of a highly specialised head in both groups, indicating that Hox gene involvement in the control of cephalic structures was acquired independently during evolution in vertebrates and invertebrates to regulate the genes required for head innovation.